Pemanfaatan Kunyit dan Getah Pepaya untuk Analisis Formalin dan Boraks Secara Sederhana di Desa Semangat Dalam - Fauzi, Muhammad; Ramadhani, Juwita; Hasniah, Hasniah (Kolaborasi Masyarakat, 2025)
Education about the dangers of borax and formalin and training in making kits to detect borax and formaldehyde content are part of this activity. With the help of natural ingredients such as turmeric and papaya sap, people, especially housewives, can identify the formaldehyde and borax content themselves. The UNISKA MAB Banjarmasin Faculty of Pharmacy Community Service Team carries out community service in Semangat Dalam Village in Handil Bakti Barito Kuala, South Kalimantan. The methods used are lectures, questions and answers, and demonstrations. The results show that this activity can help overcome participants' limited knowledge about the dangers and how to identify formaldehyde and borax in food by using simple detection tools made from natural ingredients.